Ultrasound requested by general practitioners or for symptoms unrelated to the thyroid gland may explain higher prevalence of thyroid nodules in females. - Germano, A (2019)
BACKGROUND: A higher prevalence of thyroid nodules/carcinoma in females is well-known from the literature. The reasons for this difference are not fully explained. We intended to assess gender variation in the referral for ultrasound-guided fine needle aspiration (FNA) of thyroid nodules, to study reasons for gender referral differences, and to assess differences in nodules characteristics between genders. METHODS: Included were 272 consecutive patients, with 290 nodules submitted to FNA. Patients were questioned on the reason why ultrasound (US) examination was required. Electronic medical records were reviewed. Nodules' ultrasound/cytological characteristics were assessed. Variables studied: referral cause; referral pattern (hospital-specialist versus general-practitioner); number of nodules; age, thyroid function; nodule size, TIRADS classification, resistive index, Doppler pattern, Bethesda categorisation. Variables were compared between males and females referred for FNA. Significant variables were assessed with logistic regression. RESULTS: Of the 272 patients, 215(79%) were women with a female:male referral ratio for FNA of 3.8:1. Non-parametric statistically significant differences (p < 0.05) were found between genders in: thyroid function, nodule size, referral pattern and referral cause. Nodule size and thyroid function tests became non-significant in logistic regression. Cause and referral pattern remained significantly associated with gender. Referral by a general-practitioner was associated with a 2.6-fold increase in odds of referring a female. Causes unrelated to the thyroid were associated with a 3.2-fold increase in odds of female reference. CONCLUSIONS: A referral bias might be responsible for the higher rate of thyroid nodules in female patients, both due to referral by general practitioners and due to causes indirectly related to the thyroid gland.